Address by Irina Bokova, Director-General of UNESCO, on the occasion of a lecture at the University of Iceland: From language to knowledge: how to mobilize our ultimate renewable resource?; Reykjavik, 26 May 2014 - UNESCO. Director-General, 2009-2017 (Bokova, I.G.) (26 May 2014, 2014)
Electronic version only